Characteristics of transplant athletes competing at national and international transplant games - Hames, T.; Leddington-Wright, S.; Thake, C. D.; Price, M. (BMJ Open Sport & Exercise Medicine, 2022)
Objective To describe the characteristics of athletes with solid-organ transplants (TxA) attending the British and World Transplant Games.